2013
DOI: 10.1366/13-07066
|View full text |Cite
|
Sign up to set email alerts
|

Line Selection and Parameter Optimization for Trace Analysis of Uranium in Glass Matrices by Laser-Induced Breakdown Spectroscopy (LIBS)

Abstract: Laser-induced breakdown spectroscopy (LIBS) has been evaluated for the determination of uranium in real-world samples such as uraninite. NIST Standard Reference Materials were used to evaluate the spectral interferences on detection of uranium. The study addresses the detection limit of LIBS for several uranium lines and their relationship to non-uranium lines, with emphasis on spectral interferences. The data are discussed in the context of optimizing the choice of emission lines for both qualitative and quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 43 publications
(47 reference statements)
3
33
0
Order By: Relevance
“…Since last ten years, laser-induced breakdown spectroscopy (LIBS) has been demonstrated as an efficient tool for elemental analysis in transparent or translucent dielectric materials, glasses or crystals, for applications required in many fields such as archeological research [1][2][3], forensic investigation [4][5][6], nuclear waste storage [7][8][9], or gemstone identification and qualification [10][11][12]. In the fundamental point of view, laser ablation of transparent or translucent dielectric materials corresponds to specific processes which are distinguished from what happens in laser ablation of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Since last ten years, laser-induced breakdown spectroscopy (LIBS) has been demonstrated as an efficient tool for elemental analysis in transparent or translucent dielectric materials, glasses or crystals, for applications required in many fields such as archeological research [1][2][3], forensic investigation [4][5][6], nuclear waste storage [7][8][9], or gemstone identification and qualification [10][11][12]. In the fundamental point of view, laser ablation of transparent or translucent dielectric materials corresponds to specific processes which are distinguished from what happens in laser ablation of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Trace concentrations of U have been detected, with detection limits determined to be in the parts per million (ppm) range. [10][11][12] Various ambient environments have also been explored for detection of bulk SNMs, including air and Ar at various pressures. 13 As U has a very complex atomic structure with closely packed emission lines, high spectral resolution is a crucial figure of merit.…”
Section: Introductionmentioning
confidence: 99%
“…Typically all emission lines show a maximum width closer to the target as well as at early times where the Stark effect is predominant. Recently Choi et al [8] evaluated the FWHM of U I and U II transitions with time and found that adequate isotopic separation is possible at later times to determine isotopic ratios. Their time…”
Section: Resultsmentioning
confidence: 99%
“…LA-Laser Absorption Spectroscopy (LA-LAS) is an extremely sensitive method capable of probing elemental as well as isotopic ground and excited state populations [4,5]. LA -Optical Emission Spectroscopy (LA-OES), commonly called Laser Induced Plasma Spectroscopy (LIPS) or Laser Induced Breakdown Spectroscopy (LIBS), provides another dimension to LA-hyphenated techniques in nuclear forensics where light emission from the plasma plume is analyzed [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation